1996
DOI: 10.1001/archinte.156.14.1506
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital administration of aspirin in patients with unstable angina and acute myocardial infarction

Abstract: Both experimental and clinical studies suggest that the prehospital administration of aspirin may be beneficial in patients with unstable angina and acute myocardial infarction. Experimental studies indicate that within 1 hour of aspirin administration, serum levels peak and significant inhibition of platelet aggregation occurs. Clinical studies demonstrate that early treatment with aspirin reduces mortality and reinfarction rates in patients with unstable angina and acute myocardial infarction. However, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Aspirin reduces mortality by 23%1 by mechanisms that make its delivery time sensitive 4. The mortality benefit of aspirin administered early in the care of a patient with myocardial infarction makes the prehospital administration of aspirin standard of care in most Emergency Medical Service (EMS) systems 4–7…”
Section: Introductionmentioning
confidence: 99%
“…Aspirin reduces mortality by 23%1 by mechanisms that make its delivery time sensitive 4. The mortality benefit of aspirin administered early in the care of a patient with myocardial infarction makes the prehospital administration of aspirin standard of care in most Emergency Medical Service (EMS) systems 4–7…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested improved outcomes with earlier aspirin administration for patients with acute myocardial infarction. 1517 …”
Section: Discussionmentioning
confidence: 99%
“…Gegenwärtige Therapierichtlinien empfehlen die kombinierte Behandlung mit unfraktioniertem Heparin und Aspirin für die Behandlung von Patienten mit akuten Koronarsyndromen [67][68][69]. Die maximale Dauer der Behandlung mit unfraktioniertem Heparin über den Perfusor sollte 48 Stunden nicht überschreiten, zumal durch eine längere Behandlung ein höheres Risiko für das Auftreten von Tod oder Myokardinfarkt resultieren kann [70].…”
Section: Unfraktioniertes Heparinunclassified